Использование информационных технологий в активизации групповой работы обучающихся - Кенбаева, З.Х. (My University, 2016)
Development of information competence of the students was a factor stimulating teachers searching for new forms and methods of use of ICT. One of the potential of ICT is now - is the use of computer didactic games in the formation of educational skills and abilities of students. In level courses also attached importance to the use of ICT in teaching students.
Keywords: ICT; didactic game; group work